2011
DOI: 10.1530/eje-10-0929
|View full text |Cite
|
Sign up to set email alerts
|

CDKN1B V109G polymorphism a new prognostic factor in sporadic medullary thyroid carcinoma

Abstract: Context: CDKN1B encodes the cyclin-dependent kinase inhibitor p27Kip1 and is mutated in multiple endocrine neoplasia-like syndromes. CDKN1B also harbors single nucleotide polymorphisms; the T/G transversion at nucleotide 326 (the V109G variant) has been reported to be protective in breast, hereditary prostate, and pancreatic tumors. Association of CDNK1B mutations or polymorphisms with sporadic medullary thyroid carcinoma (MTC) has not been investigated yet. Objective and design: We screened germline DNA from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
3
27
0
1
Order By: Relevance
“…In contrast, rs2066827 was not associated either with sporadic counterpart of MEN2-component neoplasias or with MTC or pheochromocytoma groups (PO0.05 in all models tested). To our knowledge, this is the first study that investigated p27 polymorphisms in pheochromocytoma, while two independent reports that were recently published analyzed the role of p27 variants in European MTC cohorts (Landa et al 2010, Pasquali et al 2011. In accordance to our results for Brazilian MTC patients, no association of p27-V109G with increased risk of sporadic MTC was observed in a large cohort of Spanish MTC cases, while a borderline significance was observed in the analysis of tumor risk of Italian MTC patients (Landa et al 2010, Pasquali et al 2011).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, rs2066827 was not associated either with sporadic counterpart of MEN2-component neoplasias or with MTC or pheochromocytoma groups (PO0.05 in all models tested). To our knowledge, this is the first study that investigated p27 polymorphisms in pheochromocytoma, while two independent reports that were recently published analyzed the role of p27 variants in European MTC cohorts (Landa et al 2010, Pasquali et al 2011. In accordance to our results for Brazilian MTC patients, no association of p27-V109G with increased risk of sporadic MTC was observed in a large cohort of Spanish MTC cases, while a borderline significance was observed in the analysis of tumor risk of Italian MTC patients (Landa et al 2010, Pasquali et al 2011).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the coding 326TOG (V109G) allelic variant has been associated with cancer risk and progression of different tumors including prostate cancer (Kibel et al 2003), oral squamous cell carcinoma (Li et al 2004), invasive epithelial ovarian cancer (Gayther et al 2007), highgrade breast tumors (Tigli et al 2005), and pancreatic carcinoma (Chen et al 2010). A recent study has shown that the variant G allele at position 326 protects against thyroid cancer development (Pasquali et al 2011), so that the role of the V109G polymorphism in increasing/ decreasing tumor risk remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The CDKN1B V109G polymorphism was reported to influence the clinical course of patients presenting sporadic MTC (15). In addition, cell cycle and apoptosis regulators have long been recognized as critical in the initiation of malignant cell proliferation and this study has recently demonstrated the influence of the presence of a C homozygous allele for the TP53 gene on the susceptibility to s-MTC (17).…”
Section: Introductionmentioning
confidence: 67%
“…Nine polymorphisms were genotyped: CDKN1A (rs1801270 and rs1059234), CDKN1B (rs2066827 and rs34330), CDKN2A (rs11515), CDKN2B (rs2069426, rs3731239, and rs1063192), and CDKN2C (rs12885) using the TaqMan system (Applied Biosystems), as described previously (17). These SNPs were chosen because they have previously been associated with thyroid carcinoma or other tumor risks as described in Table 1 (13,15,16,20,21,22).…”
Section: Genotypingmentioning
confidence: 99%
See 1 more Smart Citation